2023
DOI: 10.3389/fcimb.2023.1106591
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of HIV-1 Nef in regulating the ubiquitination of cellular proteins

Abstract: Our recent data established that HIV-1 Nef is pivotal in determining the fate of cellular proteins by modulating ubiquitination. However, it is unknown which proteins are ubiquitinated in the presence of Nef, a question critical for understanding the proliferation/restriction strategies of HIV-1 in infected cells. To identify cellular proteins ubiquitinated by Nef, we conducted a proteomic analysis of cellular proteins in the presence and absence of Nef. Proteomic analysis in HEK293T cells indicated that 93 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Although extensive HIV research has identified viral-host protein interactions that disrupt autophagy [52,53], recent studies further demonstrate dysregulation in other proteostasis mechanisms. The expression of many molecular chaperones, particularly heat shock proteins, are altered with high viremia during acute HIV [54] and auxiliary HIV protein Nef can modulate the ubiquination of various cellular proteins, either increasing their stability or promoting degradation [55,56].…”
Section: Biological Aging Hallmarksmentioning
confidence: 99%
“…Although extensive HIV research has identified viral-host protein interactions that disrupt autophagy [52,53], recent studies further demonstrate dysregulation in other proteostasis mechanisms. The expression of many molecular chaperones, particularly heat shock proteins, are altered with high viremia during acute HIV [54] and auxiliary HIV protein Nef can modulate the ubiquination of various cellular proteins, either increasing their stability or promoting degradation [55,56].…”
Section: Biological Aging Hallmarksmentioning
confidence: 99%